MEMULAI, MELAKSANAKAN, DAN MENYELESAIKAN PERUBAHAN DI SEKOLAH - Vitalis Tarsan (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
Abstract: Schools that are able to survive in the future are schools that embraced change. Not only embracing but managing it cleverly. Schools must be changed because the world around them changes too. When a school plans a change, it must be started from the planning of the change itself, which is determining what must be made, who changes it, when it is changed, why it is changed, and how it is changed. After everything was clear, then the school entered the movement stage. In the process of movement, schools must break through comfort zones, sell the change, strengthen individual capacity, provide financial support and facilities and strengthen school governance systems. After the school community is able to stand up, run, and race in the expected changes; then the school ensuring whether the planned changes have been carried out according to the plan or not. Then the school needs to do an evaluation and subsequently, make continuous improvements. And finally, give credit to the people involved in the change and celebrate the success of the change together.